Common errors in temporary hemodialysis catheter insertion. Issue 5 (4th April 2019) - Samaha, Daniel; Clark, Edward G.
Abstract: Non‐tunneled hemodialysis catheter (NTHC) insertion is an essential skill for nephrology practice and remains a requirement of training. However, improper insertion technique can increase the risk of potentially fatal infectious and mechanical complications. Evidence‐based strategies can reduce the rates of such complications and should be integrated into practice and training. Ultrasound (US) guidance should routinely be used for NTHC insertion at the femoral and internal jugular sites (with avoidance of the subclavian site). Nephrologists should receive proper training in the use of US for line insertion. With respect to other aspects of the procedure, proper insertion technique readily prevents guidewire‐induced arrhythmias. In addition, adherence to infection‐control guidelines results in a sustainable reduction in bloodstream infections. All these aspects of NTHC insertion may be best taught and evaluated through a program that includes simulation‐based mastery learning (SBML) training. As a separate issue, nephrologists (and intensivists) should be aware that a dysfunctional catheter should be replaced at a new site rather than being changed over a guidewire. This review of common errors related to NTHC insertion seeks to highlight evidence‐based approaches to practice and training.